Penyiraman Otomatis Pada Tanaman Atap Rumput Gajah - Muhammad Izzuddin Al-Muqorrobin; Anna Nur Nazzilah Chamim (Semesta Teknika, 2015)
Watering is an important step to mantain the condition of a plant, but most people dont know how good watering is, like the time of watering, watering composition that match with the plant. Almost all of green roof in any type is not using automatic system but manually watering it, that make watering the green roof become very hard to do. In this case, many people think that having a green roof is very difficult, especially in maintain it. From this problem, writer want to convince people that having a green roof is not as difficult as it look. With combining the watering methode, green roof, and surface irrigation, then writer want to make something that can help people to mantain plant especially green roof plant. The objective of this papers is to make and to know how Green Roof Automatic Watering System’s work. Using Atmega16 chip, writer made an electronic circuit that programmed by C language that will automatically watering the plant if the sensor detect the percantage above 10%. The sensor is a couple of bar that transmit voltage in between the bar past through the soil. The sensor then will transmit the data to Chip to be processed, and if they meet the condition, the IC MOC3021 will be activated, then the AC Current will automatically charge the load (pump). This electronic circuit then applied to a prototype of extensive green roof with 30’ which is a diagonal. Layering of the green roof from the first to the last is waterproof, cubical fern root (to maintain water cyclus), soil, and the plant (especially grass type). From the application, writer can make a conclusion that this green roof automatic watering system work well and can stand up to 1 month use.